Luctus est istic tuus,/ crimen novercae. Boskie i ludzkie szaleństwo Heraklesa na podstawie tragedii Eurypidesa i Seneki (Luctus est istic tuus,/ crimen novercae. Divine and human madness of Heracles according to the dramas by Euripides and Seneca) - Karamucka, Magdalena (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2013)
The article aims to examine the tragedies: Ήρακλής μαινόμενος by Euripides and Hercules Furens by Seneca and exactly the different types of the madness, by which the main character is overcome in the above mentioned dramas. Although the article touches also on the issue of the insanity sent to the hero by Hera/ Juno, concentrates especially on the fit of madness, that is here defined as a human madness.